SILENCE TO CONFIDENCE: DRAMA PEDAGOGY IN AN ISLAMIC JUNIOR HIGH SCHOOL - Abdul Yongky Syaputra; Johanes Sapri; Syafryadin Syafryadin; Syisva Nurwita (Linguists : Journal of Linguistics and Language Teaching, 2026)
Speaking reluctance remains a persistent challenge in lower-secondary English as a Foreign Language (EFL) classrooms, particularly when learners associate oral participation with public error, peer judgment, and loss of confidence. This qualitative case study examined how drama pedagogy shaped speaking participation, classroom engagement, and confidence in an eighth-grade classroom at MTsN 2 Kota Bengkulu, an Islamic junior high school in Indonesia. Data were collected through four classroom observations, a semi-structured teacher interview, and students' written reflections, and were analysed using thematic analysis. The findings show that drama pedagogy supported speaking through role-mediated participation, collaborative rehearsal, embodied and gradual performance, and deliberate teacher scaffolding. The study contributes a process-oriented understanding of drama pedagogy in a madrasah EFL context by explaining how roles, peer interaction, embodiment, and culturally responsive classroom organization can transform silence into safer, more meaningful oral participation.